Effets Des Risques Climatiques Sur La Production Vivriere Dans La Commue De Lokossa (Benin) - BAMAHOSSOVI, Christian; DJESSONOU, Franco-NÃ©o S. C.; AKINDELE, Akibou A.; OGOUWALE, Euloge (European Scientific Journal, ESJ, 2016)
The present study is a contribution to a better knowledge of the effects of the climatic risks on agriculture in the Commune of Lokossa. The analysis of the climatological data (heights of rains and temperature) of the ASECNA (1973-2012) made it possible to determine the climatic risks. That of the agricultural data (1995-2012) made it possible to study the evolution of the agricultural outputs. Socio-anthropological information made it possible to apprehend the incidences of the climatic risks. By the results obtained show that the floods (97 % of surveyed) and the drynesses (88 % of surveyed) are the major climatic risks and recurring of the Commune of Lokossa. They appear through the delay in the starting of the rains, the insufficiency heights of rain due to the recurring ruptures of the precipitations recorded during rainy seasons as well as the lengthening of the dry seasons (99 % of surveyed). Supervening of the aforesaid risks generated floods of the fields and fading of the cultures (79 % of surveyed) and caused during fifteen last years of the falls of the agricultural productions (15 % Zea mays, 20 % Vigna unguiculata, 17 % Arrachis hypogea).